Planning and Setting Up of a Communication Program for Hospitalized COVID-19 Patients: Challenges and Potential Solutions in Resource Constrained Setting - Samridhi Nanda (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Background The recent onset of COVID-19 pandemic has necessitated many patients to be hospitalized in the COVID-19 treating centers. Owing to the need for isolation of these patients and minimizing the risk of transmission to healthy people, COVID-19-positive patients are completely restricted from meeting their friends and families. This gives rise to anxiety amongst the patients' relatives as they are not able to monitor the progress of the patients and have to depend entirely on the healthcare staff for any updates regarding the patient. In contrast, the treating doctors are undergoing severe stress due to the unknown nature of the virus and the risks involved in treating patients. They are thoroughly exhausted after the long hours donning the personal protection equipment (PPE). Objective To structure and form an interface for communication between the treating physician and the families, as a “communication team,” to decrease the workload on the treating physicians and minimize their contact time in a COVID-19 setting. Results The addition of a communication team improved the physicians' efficiency of patient management and family satisfaction. Several challenges were faced during the setting up of this interface effectively. However, most of these were dealt with along the way. The communication team was instrumental in allaying the anxiety of the family with respect to their patients' clinical condition. This also ensured engagement of doctors from non-clinical and laboratory-based departments in the COVID-19 treatment process. Conclusion Adding up a communication team for communicating clinical updates to the family in a resource-limited scenario greatly improved communication and thus family satisfaction of the COVID-19-positive patients.